A Survey Study To Identify Tehran University Of Medical Science Faculties' Member's Familiarities With Open Access Movement And Their Attitude About It - Mohammadhiwa Abdekhoda; Moahmmadreza Alibeyk; Agha Fateme Hossini; Saman Ravand; Masoud Mohammadi; Javad Zarie (Tehran University of Medical Sciences, 2014)
Background and Aim: Open access to scientific information is a new paradigm in scientific communication that facilitates access to research. This study was carried out to identify Tehran University of medical science faculties members' familiarities with Open access and to survey their attitude about it. Materials and Methods: A descriptive survey method was applied. The study population consisted of 163 members of Tehran University of Medical Sciences. Data gathering tool was questionnaires that its validity and reliability was confirmed. Data was collected and analyzed by SPSS software and descriptive statistic methods. Results: Results show that more than 50 percent of population have modest familiarites with Open acces. Furthermore, the faculties's members familiarites with Open access technique was moderate. More than 70 percent (114 person) of them have positive attitude toward Open access and it's techniques. Conclusion : Faculties members' familiarity with Open access relatively is low but when they received information about the concept, rules and aim of this paradigm, their attitudes positively changed. Therefore, open access should be considered as a perfect method in scientific communication.